Parental psychological control and cyberbullying tendency in adolescents from the perpetrator side - Alifia Yuniar Rahmaputri; Setiasih Setiasih; Ni Putu Adelia Kesumaningsari (University of Muhammadiyah Malang, 2022)
This research aims to analyze the contributions of parents’ behavior to adolescent cyberbullying. It tests the role of parental psychological control and adolescent cyberbullying behaviour using a quantitative design with the selection of samples in the form of accidental sampling. Furthermore, the participants comprised 383 adolescents aged 13-17 years who live with both parents and have committed cyberbullying. The respondents filled out the questionnaires containing the Psychological Control – Disrespect Scale (PCDS) to measure the patent’s psychological control and the Cyber-Aggression Scale (CYB-AGS). A multiple regression analysis showed that the control predicts adolescent cyberbullying behavior (R2= 0,053, F =10.619, p = 0.000), and as a predictor variable, it contributes 5.3% to cyberbullying behavior. According to the model, the father’s psychological control predicts adolescents’ cyberbullying behavior. This research reveals the significance of parental psychological control in adolescent cyberbullying behaviour.